COMPARATIVE ANALYSIS OF VIRULENCE FACTOR BETWEEN DIFFUSIBLE SIGNAL FACTOR BIOSENSOR AND INDONESIAN Xanthomonas oryzae pv oryzae - Fatimah Fatimah (National Research and Innovation Agency, Republic of Indonesia (BRIN), 2021)
Xanthomonas oryzae pv. Oryzae (Xoo) is the causal agent of bacterial blight in rice (Oryza sativa L.). In the understanding of virulence determinants of three Indonesian Xoo, extracellular polysaccharide (EPS) production, cellulose and diffusible signal factor (DSF) were identified. DSF signaling system in Xoo is involved in the regulation of virulence factor production. In this study the comparative analysis was conducted with the DSF biosensor isolate (Xoo-dsf). The results showed that high yield of EPS and cellulose activity revealed from isolate Xoo1130 and Xoo1122 compare to Xoo93229 while Xoo-dsf giving similar result with Xoo1130. The comparative analysis of Xoo1130 and Xoo-dsf showed that Xoo1130 produced three DSF-family signals (DSF, BDSF and CDSF) similar to the DSF biosensor isolate. It assumed that Xoo1130 uses a similar mechanism in Xoo-dsf to autoregulate the biosynthesis of the DSF-family signals.